Inter-Industry wage differentials and earnings inequality in Brazil - Castelar, Armando; Ramos, Lauro (Estudios de Economía, 2016)
This paper shows that there is a large inter-industry wage dispersion in the Brazilian labor market, that persists after controlling for differences in workers’ productive attributes and job characteristics. The wage structure is robust over time, with no evidence that wage premiums can be imputed to differences in job quality, workers’ heterogeneity, discriminatory practices, short-run excess demand in specific sectors, or changes in the macroeconomic and political settings. The contribution of labor market segmentation to wage inequality is estimated to be in the 7-11 percent interval.